REPAIRx, a specific yet highly efficient programmable A > I RNA base editor. (15th October 2020) - Liu, Yajing; Mao, Shaoshuai; Huang, Shisheng; Li, Yongqin; Chen, Yuxin; Di, Minghui; Huang, Xinxin; Lv, Junjun; Wang, Xinxin; Ge, Jianyang; Shen, Shengxi; Zhang, Xiaoming; et al.
Abstract: Programmable A > I RNA editing is a valuable tool for basic research and medicine. A variety of editors have been created, but a genetically encoded editor that is both precise and efficient has not been described to date. The trade‐off between precision and efficiency is exemplified in the state of the art editor REPAIR, which comprises the ADAR2 deaminase domain fused to dCas13b. REPAIR is highly efficient, but also causes significant off‐target effects. Mutations that weaken the deaminase domain can minimize the undesirable effects, but this comes at the expense of on‐target editing efficiency. We have now overcome this dilemma by using a multipronged approach: We have chosen an alternative Cas protein (CasRx), inserted the deaminase domain into the middle of CasRx, and redirected the editor to the nucleus. The new editor created, dubbed REPAIRx, is precise yet highly efficient, outperforming various previous versions on both mRNA and nuclear RNA targets. Thus, REPAIRx markedly expands the RNA editing toolkit and illustrates a novel strategy for base editor optimization. Synopsis: Development of CRISPR/Cas9 programmable RNA base editors that exhibit both high efficiency and high specificity has proven challenging. A multipronged approach overcomes this limitation and allowed engineering of an optimized A > I RNA base editor, REPAIRx. Previously developed A > I editors based on ADAR2 deaminase fusion to dCas13b (REPAIRv1) cause substantial off‐target effects in the transcriptome. Off‐target effect‐reducing mutations in the ADAR2 deaminase domain (REPAIRv2) also significantly decrease on‐target editing. Fusion to an alternative targeting moiety (dCasRx), deaminase domain insertion in its middle, and nuclear localization of the fusion protein, yields a precise yet highly specific A > I editor. Nuclear localization of dCasRx allows editing of nuclear DNA in addition to cytoplasmic targets. Abstract : A multipronged approach allowed engineering of an optimized A > I RNA base editor facilitating specific and efficient base editing.